2020
DOI: 10.3389/fsufs.2020.602911
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Comparison of Talc- and Peat-Based Phytobeneficial Pseudomonas fluorescens and Pseudomonas synxantha Bioformulations for Promoting Plant Growth

Abstract: Use of plant growth promoting rhizobacteria (PGPR) is an important strategy in sustainable agriculture. Among PGPR, many Pseudomonas strains are of great interest due to their abilities to colonize and thrive in the rhizosphere, in addition to displaying mechanisms in plant growth promotion and biocontrol activities. However, as Pseudomonas strains are non-spore forming micro-organisms, their development into stable bioformulations for commercial applications can be difficult. This study examined over a long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…During the first 3 weeks, both the emulsion and the control show similar viability, following which the control shows a gradual loss of the cells, whereas the emulsions maintained a viability of 10 8 CFU/mL after 10 weeks of storage. These cell viability values are in the range for reported values of peat and talc-based dry carriers after 60–90 days of storage. Furthermore, our initial bacteria concentration of 10 9 CFU/mL incorporated within the emulsions is also much lower than previously reported values mostly in the range of ∼10 11 CFU/mL .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…During the first 3 weeks, both the emulsion and the control show similar viability, following which the control shows a gradual loss of the cells, whereas the emulsions maintained a viability of 10 8 CFU/mL after 10 weeks of storage. These cell viability values are in the range for reported values of peat and talc-based dry carriers after 60–90 days of storage. Furthermore, our initial bacteria concentration of 10 9 CFU/mL incorporated within the emulsions is also much lower than previously reported values mostly in the range of ∼10 11 CFU/mL .…”
Section: Resultssupporting
confidence: 67%
“…The high cell viabilities observed for Pseudomonas simiae are particularly promising since it holds potential for the development of a suitable formulation for loading other nonsporulating PGPM such as P. fluorescens 1629RS, P. syringae 724RS, P. chlororaphis 63–28 . While some Pseudomonas strains are commercially available, their current market share represents only 6% of the total biobased agriculture industry . The lack of suitable formulation platforms is a big deterrent in utilizing them to their full potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peat is very common used carrier material globally and has high content of organic matter, water holding capacity, and simply obtainable [19]. In previous study, it was found that peat showed good efficacy in formulation, and help colonization in plant roots when peat was used for bio formulation of P. fluorescens [20]. Nakkeeran et al also observed similar potential results of peat-based formulation for P. chlororaphis shelf-life [21].…”
Section: Discussionmentioning
confidence: 85%
“…40% of the 8.3 × 10 8 CFU/g BCB16 were added to the autoclaved talc powder, and the number of microbes were counted using serial dilution method every 30 days for 4 months. Novinscak and Filion [ 43 ] found that using talc powder as a carrier material for the Pseudomonas strain resulted in a stable microbe population. Tamreihao et al [ 44 ] compared corn starch and talc powder as biofertilizer formulations and concluded that the talc formulation has a higher cell count than corn starch.…”
Section: Discussionmentioning
confidence: 99%